Pengaruh Strategi Penjualan Buku melalui Akad Khiyar terhadap Kepuasan Konsumen (Studi Kasus pada Toko Buku H. Minan Babat Lamongan) - Imro’atul Magfiroh; Abdullah Zawawi (Program Studi Ekonomi Syariah dengan Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2022)
In an effort to improve good customer service, sellers must have the ability and must be able to create a sense of responsibility to consumers in order to create good expertise in the field of customer service. By holding a khiyar contract, consumers will feel satisfied because they can choose the desired product and do not feel disadvantaged. The method used in this study is a quantitative experiment with the formulation of the problem